Preservation of black grapes by isochoric freezing - Câmpean, Ștefan I., Beșchea, G. A., Tăbăcaru, M. B., Scutaru, L. M., Dragomir, G., Brezeanu, A. I., Șerban, A., & Năstase, G. (Elsevier Ltd., 2023)
Fruits are perishable. It’s crucial to have an efficient preservation technique that may extend storage duration while maintaining the physical quality and nutritional values to avoid wastage. The majority of long-term storage solutions for fruits use refrigeration. In this study, we evaluate the potential of isochoric freezing as an alternative method of preservation for black grapes (Vitis vinifera L.). We compare the properties of black grapes preserved for 7 days in trehalose solution at − 4 ◦C in isochoric conditions (average pressure 34.2 MPa) with those of fresh black grapes and with grapes preserved isobarically in four conditions (room temperature, in the fridge, in the freezer, and in a plastic bag filled with trehalose solution). The results indicate that grapes preserved by isochoric freezing at temperatures below the freezing point of water do not lose weight; on the contrary, they resulted in a very small (2%) weight gain. Freezing under isochoric conditions did not result in significant changes in terms of macroscopic appearance, colour, firmness, ◦Brix values, or pH. We consider that isochoric freezing has the potential to be used as a preservation method for grapes while maintaining physicochemical parameters similar to those of fresh fruits.